RELEVANSI HASIL UAN TERHADAP PRESTASI BELAJAR MATA KULIAH DASAR-DASAR AKUNTANSI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI IKIP PGRI MADIUN - Elva Nuraina (Jurnal Pendidikan, 2008)
This research serves an analysis to prove the relevance of the score of National Standardized Test towards the achievement in Dasar-Dasar Akuntansi subject for the students of Accounting Department Study Program, IKIP PGRI Madiun. The population of this research cover the students of Accounting Department Study Program, semester one, term 2006/2007. Data resources of this research consist of documents taken from records of students’ standardized national test score and academic achievement record.The data are then analyzed under the statistic analysis of correlation product moment formulae by the significant rate of 95 which results in operating r of 0.279 less than table r of 0.361. This shows that the score of standardized national scores do not make any significance on the achievement in the subject of Dasar-Dasar Akuntansi I of the students of IKIP PGRI Madiun, in the way that the alternative hypothesis is rejected.